2018
DOI: 10.15282/jmes.12.1.2018.16.0310
|View full text |Cite
|
Sign up to set email alerts
|

The effect of amine substituent chain length on POSS/Polysulfone mixed matrix membrane

Abstract: The main obstacle encountered during the development of polyhedral oligomeric silsesquioxane (POSS) mixed matrix membrane (MMM) via physical blending is the combination of compatible inorganic filler and polymeric matrix. In this work, mono-functional POSS of different amine functionalised substituent chain lengths namely aminopropylisobutyl POSS (AMPOSS-a) and aminoethylaminopropylisobutyl POSS (AMPOSS-b) were incorporated into Polysulfone (PSf) membrane at 1wt%, 2wt% and 3wt% loadings. The effect of amine su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…Furthermore, glass transition temperatures (Tg) for PSU film were found at 189.15 °C. This value was in concordance with those reported elsewhere (190–200 °C) [ 66 , 67 , 68 ]. Sequentially, PSU-VIM membranes displayed a Tg range of 185.40 to 186.58 °C.…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, glass transition temperatures (Tg) for PSU film were found at 189.15 °C. This value was in concordance with those reported elsewhere (190–200 °C) [ 66 , 67 , 68 ]. Sequentially, PSU-VIM membranes displayed a Tg range of 185.40 to 186.58 °C.…”
Section: Resultssupporting
confidence: 94%
“…Figure 5a indicates that glass transition temperature ( T g ) of the PSF membrane was 182.71°C. This value was close to that (190–200°C) of most literatures 29,32,33 . The literature reported that the T g value of the PSF membrane was 142°C 34 .…”
Section: Resultssupporting
confidence: 87%
“…close to that (190-200 C) of most literatures. 29,32,33 The literature reported that the T g value of the PSF membrane was 142 C. 34 The T g value of the CM-PSF membrane decreased to 173 C, and the T g value of the T-PSF membrane further decreased to 158.24 C. This phenomenon was reported in literature 27 : The T g value of CM-PSF decreased from 183 to 158 C, which depended on the grafting degree. Higher grafting degree resulted in lower glass transition temperature.…”
Section: Thermal Behavior Of the Membranesmentioning
confidence: 68%
“…The few factors that define a membrane's effectiveness are permeability, pore structure, selectivity, hydrophilicity, and mechanical stability As for permeability which mostly affected by fouling can be control by introducing nanoparticles to altered the membrane structure [58]. Besides that, polymeric membranes are favored for their ease of fabrication and their low cost [59], however, their disadvantages are that the polymers most commonly used, namely polysulfone (PSU) which are semi-hydrophobic which can lead to reduced flux and increased fouling [60] but the polyethyleneimine had been used in this study to increase the hydrophilicity with the adding of silver nanoparticles. Silver is another commonly used nanoparticle for nanocomposite membranes: silver nanoparticles are widely known to be antimicrobial, and there are commercial home water systems currently available which use membranes or filters coated with silver nanoparticles, and these are reported to remove 99.99% of pathogens [47].…”
Section: Introductionmentioning
confidence: 99%
“…As stabilizing agent, PEI will provide increase in hydrophilicity, lowering non-intended adsorption and increase water solubility of the membrane. [60,61]. Despite the ability to increase membrane permeability, PEI also consist of cationic charge that can react with heavy metal ion either in basic or acidic environment to form a complex coordination [66].…”
Section: Introductionmentioning
confidence: 99%